1960
DOI: 10.2307/4590966
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Animal Rabies in Florida

Abstract: Isolated cases of rabies in dogs, house cats, foxes, raccoons, and skunks were investigated for clues to the existence of an inapparent reservoir of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 3 publications
2
17
0
Order By: Relevance
“…Several authors have previously reported lyssavirus isolation from the brains and salivary glands of apparently healthy, normal-behaving bats taken from the wild (Scatterday, 1954;Burns et al, 1956). Sporadic reports suggest the existence of a 'carrier state' of rabies among asymptomatic free-ranging bats (Pawan, 1936a, b;Sulkin, 1962;Rønsholt et al, 1998;Echevarría et al, 2001;SerraCobo et al, 2002;Wellenberg et al, 2002;Aquilar-Sétien et al, 2005).…”
Section: *Only Histological Examination Was Performed (No Pcr)mentioning
confidence: 99%
“…Several authors have previously reported lyssavirus isolation from the brains and salivary glands of apparently healthy, normal-behaving bats taken from the wild (Scatterday, 1954;Burns et al, 1956). Sporadic reports suggest the existence of a 'carrier state' of rabies among asymptomatic free-ranging bats (Pawan, 1936a, b;Sulkin, 1962;Rønsholt et al, 1998;Echevarría et al, 2001;SerraCobo et al, 2002;Wellenberg et al, 2002;Aquilar-Sétien et al, 2005).…”
Section: *Only Histological Examination Was Performed (No Pcr)mentioning
confidence: 99%
“…The first descriptions of rabies-virus infection in bats in the United States were published .50 yr ago (Scatterday, 1954;Sulkin and Greve, 1954;Venters et al, 1954). Since that initial recognition, rabiesvirus infection is recognized as enzootic in bats in the United States and Canada, and the virus has been detected in all known species of bats in these countries (Constantine, 1979;Brass, 1994;Streicker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous bat rabies was first recognized in the USA in 1953 (Scatterday & Galton, 1954), although the exact age of its emergence remains uncertain. During 2001, bats were responsible for 17 % of reported wildlife rabies cases and all three cases of human rabies in the USA (Krebs et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…RNA viruses are characterized by a high mutation rate during replication due to the lack of proofreading and postreplication error correction by RNA polymerases (Domingo & Holland, 1994). This genetic diversity seems to provide an adaptive potential for RV that can vary according to natural history (Morimoto et al, 1998; Kissi et al, 1999).Indigenous bat rabies was first recognized in the USA in 1953 (Scatterday & Galton, 1954), although the exact age of its emergence remains uncertain. During 2001, bats were responsible for 17 % of reported wildlife rabies cases and all three cases of human rabies in the USA (Krebs et al, 2002).…”
mentioning
confidence: 99%